Pathways of Women Prisoners to Jail in Pakistan - Adeela Khalid; Nashi Khan (Tabriz University of Medical Sciences, 2013)
Background: The present study aimed to examine pathways to imprison¬ment for women in Pakis¬tan. It was hypothesized that early life victimiza¬tion in women, problematic family relationship and economical depriva¬tion would be significantly associated with criminal activities of women prisoners.Method: To identify the pathways to prison, structured interview was de¬vised by the researchers. Sample comprised of 114 women prisoners en¬listed from KotLakhpat jail, Lahore, Pakistan. Re¬sults: Poverty, revenge, anger and lack of empowerment were signifi-cantly associated with crimi¬nal activities of women offender. Conclusion: The umbrella of rehabilitation should also cover social and legal matters of women of¬fenders along with tackling their psychological issues.